JARINGAN AD-HOC VEHICULAR (VANET) : TINJAUAN TENTANG ARSITEKTUR, KARAKTERISTIK, APLIKASI, DAN PROTOKOL MEDIUM ACCESS CONTROL (MAC): Rosida Nur Aziza - Jurnal, Redaksi Tim (PETIR, 2019)
VANET (Vehicular Ad-hoc Network) is an ad-hoc wireless network which nodes are composed by mostly moving vehicles and infrastructure communications or access points along the road. It integrates adhoc networking, cellular technology, wireless LAN and other technologies, which include GPS(Global Positioning System), digital mapping, sensing technologies and advanced information processing tools to support Intelligent Traffic Systems (ITS). VANET is developed mainly to improve road safety and to increase the traffic efficiency. It is designed to support the exchange of warning messages among the vehicles to increase the passenger safety and other information related to VANET applications and services . To achieve these goals, there are several issues that should be addressed. One of these challenges is designing reliable and efficient Medium Access Control (MAC) protocol for VANET. Due to VANET’s distinguishing characteristics, such as high mobility of the nodes, dynamic network topology, enough battery power, high processing power, etc, the MAC protocols designed for MANET (Mobile Ad-hoc Network) are not suitable for VANET. The research community has been working to develop MAC protocols appropriate for this ad-hoc network by proposing new design or modifying the existing one. In this paper, the VANET’s architecture, characteristics, applications and standard are discussed and then a comprehensive study of several MAC protocols available in the literature is presented.